Kurtosis of height fluctuations in (1 + 1) dimensional KPZ dynamics. (19th May 2015) - Singha, Tapas; Nandy, Malay K
Abstract: We study the fourth order normalized cumulant of height fluctuations governed by 1 + 1 dimensional Kardar–Parisi–Zhang (KPZ) equation for a growing surface. Following a diagrammatic renormalization scheme, we evaluate the kurtosis Q from the connected diagrams leading to the value Q  = 0.1523 in the large-scale long-time limit.